Pengaruh Keterlibatan Kerja, Motivasi Intrinsik dan Kepuasan Kerja terhadap Komitmen Kerja Pegawai Dinas Kesehatan Kabupaten Pemalang - Rossalinda Ayu Saffira; Mohammad Fauzan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The purpose of the study was to explain and analyze (1) the effect of work involvement on employee work commitment (2) the effect of intrinsic work motivation on employee work commitment (3) the effect of job satisfaction on employee work commitment of Pemalang District Health Office employees. This research is a type of explanatory research (explanatory research) Research sample of 100 employees using Purposive sampling Data obtained through the distribution of questionnaires using the googleform application. Respondents who fill out a complete questionnaire become data that can be analyzed. For the benefit of data analysis carried out instrument test, model test and hypothesis test. Testing using SPSS version 25. The findings of the research are (1) work involvement has a positive effect on employee work commitment, (2) intrinsic motivation has a positive effect on employee work commitment (3) job satisfaction has a positive effect on the work commitment of Pemalang District Health Office employees; Based on research findings that show employee work commitment is influenced by work engagement, intrinsic motivation and job satisfaction indicate that the work environment at the Pemalang District Health Office is conducive and needs to be maintained so that employee work commitment continues to increase